Synthesis of 3-Phenylimino-4-aroyl/acyl-6-aroyl/acyl hydrazino-1,2,4,5-dithiadiazine - Choudhari, J.R.; Berad, B.N. (Asian Journal of Chemistry, 2016)
Several 3-phenylimino-4-aroyl/acyl-6-aroyl/acyl hydrazino-1,2,4,5-dithiadiazines have been synthesized by one step condensation reaction of N-phenyl-S-chloroisothiocarbamoyl hloride and bis-1,5-aroyl/acyl-3-thiocarbohydrazides followed by basification of resultant ompounds. The structures of the compounds were established on the basis of elemental analysis and spectral studies.